Exciton dissociation in the presence of phonons : a reduced hierarchy equations of motion approach - Yao, Yao (2014)
Combining the reduced hierarchy equations of motion (HEOM) approach with the Wigner-function formalism, we investigate nonperturbatively exciton dissociation under the influence of a phonon bath in an organic heterojunction. The exciton is modeled by an electron-hole pair with the electron moving in the presence of both an external electric field and the Coulomb attraction potential from the hole. In the absence of a phonon bath, calculated HEOM results reproduce those from the Onsager-Braun theory in weak electric fields. In the presence of a phonon bath, substantial deviations from the Onsager-Braun theory are found, signaling phonon-induced quantum effects. Furthermore, time evolution of the spatial current distribution is examined, and an initial spike followed by a polarity change of the transient photocurrent have been recovered.